2008
DOI: 10.1016/j.mri.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging features of fibrocystic change of the breast

Abstract: Purpose-Studies specifically reporting MR imaging of fibrocystic change (FCC) of the breast are very few and its MR imaging features are not clearly known. The purpose of this study was to analyze the MR imaging features of FCC of the breast.Materials and Methods-Thirty one patients of pathologically proved FCC of the breast were retrospectively reviewed. The MRI study was performed using a 1.5 T MR scanner with standard bilateral breast coil. The imaging protocol consisted of pre-contrast T1W imaging and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…Further, benign lesions manifesting as nonmasslike enhancement may have suspicious kinetic features, including rapid early enhancement or plateau or washout patterns (11,15,16,35). In one series, investigators reviewing the MR imaging features of biopsy-proved fibrocystic changes found a wide spectrum of morphologic and kinetic features, including both focal and more diffuse distributions, with both benign and malignant types of kinetic curves (37). Hence, in the MR imaging interpretation of nonmasslike enhancement, the morphologic characteristics should take precedence over the kinetic features in the BI-RADS assessment and clinical management.…”
Section: Pitfalls In Interpretation Overreliance On Kinetic Informationmentioning
confidence: 99%
“…Further, benign lesions manifesting as nonmasslike enhancement may have suspicious kinetic features, including rapid early enhancement or plateau or washout patterns (11,15,16,35). In one series, investigators reviewing the MR imaging features of biopsy-proved fibrocystic changes found a wide spectrum of morphologic and kinetic features, including both focal and more diffuse distributions, with both benign and malignant types of kinetic curves (37). Hence, in the MR imaging interpretation of nonmasslike enhancement, the morphologic characteristics should take precedence over the kinetic features in the BI-RADS assessment and clinical management.…”
Section: Pitfalls In Interpretation Overreliance On Kinetic Informationmentioning
confidence: 99%
“…This feature is highly indicative of fibrocystic mastopathy [36]. We believe that it is not sufficiently used, because many studies in which MRI features of fibrocystic changes were analysed did not report T 2 weighted sequences in their protocol [37,38].…”
Section: Non-mass-like Enhancementmentioning
confidence: 99%
“…However, dynamic contrast-enhanced MRI studies are limited because enhancement patterns are similar for mucinous carcinoma and fi broadenoma 4 and for intraductal papilloma or fi broadenoma containing a rich blood fl ow and a malignant tumor and because normal breast tissue and focal fi brocystic disease show spotty enhancement. 5 Diffusion-weighted imaging (DWI) has become widely accepted in body imaging to detect and characterize focal malignant lesions. [6][7][8][9][10] Recent studies have evaluated the suitability of DWI for differentiating benign and malignant tumors using apparent diffusion coefficient (ADC) values.…”
Section: Introductionmentioning
confidence: 99%